SCIENTIFIC AND THEORETICAL BASIS OF STRENGTHENING THE REVENUE BASE OF LOCAL BUDGETS - Kudaybergenova Guzal (Scholar Express Journals, 2024)
The scientific-theoretical basis of strengthening the revenue base of local budgets has been studied. The content and characteristics of local budgets are shown in detail. Also, the stages of formation of incomes of local budgets are mentioned.
Keywords: budget revenues; tax; local budget; tax policy